Kepuasan Kerja sebagai Mediator antara Kepemimpinan, Motivasi, Kompensasi, dan Lingkungan Kerja terhadap Kinerja Karyawan Generasi Z di Jakarta - Ayu Niken Shafira Putri; Putri Mega Desiana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Generation Z currently dominates the workforce in Indonesia, including in the private sector in DKI Jakarta Province. The unique characteristics of this generation such as a preference for work flexibility, self-development, and a work environment that supports values and sustainability. This study aims to analyze the influence of leadership style, motivation, compensation, and work environment on employee performance, with job satisfaction as a mediating variable on Generation Z employees in private companies in Jakarta. This study uses a quantitative approach with a causal design and survey method. Data were collected from 249 respondents with at least one year of work experience. Data testing was conducted using Structural Equation Modeling (SEM) using LISREL 8.8. The results indicate that motivation, compensation, and job satisfaction have a positive and significant direct effect on employee performance. Meanwhile, leadership style and work environment were found to have no positive effect on employee performance. In addition, job satisfaction was proven to mediate the variables of motivation, compensation, and work environment on employee performance. However, leadership style could not be mediated by job satisfaction in influencing employee performance. These findings emphasize the importance of compensation and work environment provided by companies, as well as motivational incentives to optimize the performance of Generation Z in the private sector. Furthermore, the selection of leadership styles within a company should be considered to enhance employee performance.